Gamification of Assessment Test through Multiple Question Paths to Facilitate Participants’ Autonomy and Competence - Atmaja, Pratama Wirya; Mandyartha, Eka Prakarsa (Universitas Negeri Malang, 2020)
Gamifying activities to make them more game-like is one of the hottest trends in various fields, including education. Among the factors influencing the success of gamification for education are the participants’ sense of autonomy and competence, which can be facilitated with the incorporation of multiple learning paths. However, the use of multiple question paths in gamified assessment tests is still under-studied. This mixed-method study was aimed at exploring the matter through a paper-based and gamified assessment test in higher education. A controlled experiment was conducted in a calculus course in an informatics department. The experimental group (n = 38) undertook a gamified written test, and the control group (n = 37) undertook a regular one. The gamified test consisted of several Hard and Medium Questions, and each participant would choose a question path containing some of the questions. Nine question paths were available with varying ratios between Hard and Medium Questions, and the participants were allowed to ask for two hints on the Hard ones. A questionnaire, based on the EGameFlow model, was used to assess the gamified test. The results show that the gamified test was able to facilitate the participants’ sense of autonomy but not their sense of competence, which was due to flaws of the test. Two additional positive effects of the test on the participants’ knowledge improvement and Flow experience are identified. The path selection pattern among the participants and the flaws of the gamified test are also discussed.